2001
DOI: 10.1128/jvi.75.18.8742-8751.2001
|View full text |Cite
|
Sign up to set email alerts
|

Borna Disease Virus Phosphoprotein Binds a Neurite Outgrowth Factor, Amphoterin/HMG-1

Abstract: The Borna disease virus (BDV) p24 phosphoprotein is an abundant protein in BDV-infected cultured cells and animal brains. Therefore, there is a possibility that binding of the p24 protein to cellular factor(s) induces functional alterations of infected neural cells in the brain. To identify a cellular protein(s) that interacts with BDV p24 protein, we performed far-Western blotting with extracts from various cell lines. Using recombinant p24 protein as a probe, we detected a 30-kDa protein in all cell lines ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…In CRP5-infected rats with or without encephalitis, rapid degeneration of pyramidal neurons in the CA3/4 region of the hippocampus was observed, a clear departure from the typically protracted hippocampal dentate gyrus damage usually observed following CRP3 infection (9). Thus, these studies demonstrate that in the Lewis rat, CRNP5 infection causes a significantly different disease phenotype than CRP3 infection, whether due to direct virus cytopathic effect, neuroimmune responses (8,26,36,45), or other pathogenic processes (e.g., the inhibition of the function of amphoterin, a neurite outgrowth-promoting adhesive factor, or the indication of neurotrophins) (27,58).…”
Section: Discussionmentioning
confidence: 99%
“…In CRP5-infected rats with or without encephalitis, rapid degeneration of pyramidal neurons in the CA3/4 region of the hippocampus was observed, a clear departure from the typically protracted hippocampal dentate gyrus damage usually observed following CRP3 infection (9). Thus, these studies demonstrate that in the Lewis rat, CRNP5 infection causes a significantly different disease phenotype than CRP3 infection, whether due to direct virus cytopathic effect, neuroimmune responses (8,26,36,45), or other pathogenic processes (e.g., the inhibition of the function of amphoterin, a neurite outgrowth-promoting adhesive factor, or the indication of neurotrophins) (27,58).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, we have recently found that BDV P directly interacts with a neurite outgrowth factor, HMGB1, and inhibits its function in cultured neuronal cells (18). Considering the roles of HMGB1 in neurite outgrowth, cell migration, and cellular survival in developing brains (19), it is also possible that P can affect neuronal development by inhibiting HMGB1 function in glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here we use transgenic mice expressing the phosphoprotein (P) of BDV in the CNS to understand the linkage between CNS virus infection and neurobehavioral disorders, as well as to elucidate the molecular nature of BDV neuropathogenesis. The P is abundantly expressed in infected animal brains and interferes with a multifunctional protein, HMGB1, in neuronal cells (18,19), suggestive of a neurotropic effect of this protein in the infected CNS. We demonstrate that BDV P transgenic mice develop behavioral abnormalities resembling those in BDV-infected animals, and that the transgenic brains show severe neurobiological disturbances linked to neurobehavioral disorders.…”
mentioning
confidence: 99%
“…In a recent study, it was revealed that BDV P binds directly to a multifunctional protein, HMGB1 (also called amphoterin or HMG-1), and inhibits its function in cultured neural cells (30). A line of evidence has suggested that HMGB1 plays important roles not only in the neurite outgrowth of neurons but also in cell survival through interaction with its cellular receptor, RAGE (receptor for advanced glycation end products) (36).…”
mentioning
confidence: 99%